BOUNDARY OF NONMINIMAL DERIVATIVE COUPLING(NMDC) CONSTANT USING ENERGY CONDITIONS - RIZKA TAUFANI (NIM : 20216048), MUHAMMAD
The study aims to determine the constrain of the coupling parameter ? of nonminimal derivative coupling theory(NMDC) of scalar field.. The calculation of the parameter was build from the general energy conditions combined to modified Einstein theory(i.e. the scalar filed act as the external source of gravity beside the ideal fluid). Resulting two equations that consist of of energy density ? and the momentum p, then one defined the deacceleration q to these equation. The present value of cosmological constant such as Hubble constant H, q, and scale factor a was put into the equations to determine the boundaries. The results are the parameter boundaries varies along the valid energy conditions.